Pemanfaatan Layanan Telefarmasi Di Kota Denpasar - I Made Wijaya, Ni Made Ayu Dwi Darmayanti Wijaya (Bali International University, 2022)
Background: Telepharmacy the practic of telemedicine to pharmaceutical services with the scope of the pharmacist's responsibility with time and distance to patients. In Bali, the use of drug telepharmaceutical platform access for counseling, drug information, and drug therapy monitoring with proportion in Denpasar City. Purpose: Description of utilization counseling, drug information services, and monitoring of drug therapy in telepharmacy in Denpasar City. Method: Descriptive research with analytical qualitative approach. The sampling technique in this study used purposive sampling method 100 respondent. The instrument used is a question on the use of telepharmaceutical have been tested for validity and reliability. The data were analyzed by SPSS 15.0 (Statistical Product and Service Solution) with statistical test. Result: Based the use of telepharmaceutical counseling services using suppositories was classified as required 66%, counseling on the use of hard drugs such as pain, rheumatism, and antibiotics was needed as 51%. Utilization of drug information services by telepharmacy requires an explanation of how to take medicine as 60%, the required drug information service is the duration of drug use much as 60%. The use of telepharmaceutical monitoring is need by the community, namely monitoring of antibiotic drug therapy and suppositories as much as 47%, monitoring of drug use is not needed by the community as 47%. Conclusion: The use of counseling needed as (83%), utilization of information services need as (83%), and monitoring of treatment needed much as (85%) in community telepharmaceutical service in Denpasar City. Keywords: Telepharmacy, Counseling, Drug information services, Drug therapy monitoring.